The tune of love and the nature(ness) of spacetime - Porto, Rafael A. [UNESP] (Wiley-Blackwell, 2016)
The black hole information paradox is among the most outstanding puzzles in physics. I argue here there is yet another black hole quandary which, in light of the recent direct detection of gravitational waves by Advanced LIGO, reveals a new window to probe the nature of spacetime in the forthcoming era of `precision gravity.'
Keywords: Gravity; black holes; quantum; gravitational waves